2020
DOI: 10.1111/phn.12712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of providing nursing care with web‐based program on maternal self‐efficacy and infant health

Abstract: Objective The study was conducted to examine the efficacy of a web‐based program, informed by Pender's Health Promotion Model, given to primiparous women on the growth and development of infant, infants’ health, and women's self‐efficacy level. Methods This randomized controlled study with a posttest design was conducted in three primary care clinics. The study group comprised 71 primiparous women and their infants (intervention group: N = 35; control group: N = 36). The women who are at the 33–37th gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
2
15
0
3
Order By: Relevance
“…A total of nine studies [ 4 , 5 , 7 , 8 , 11 , 12 , 14 , 17 , 19 ] reported exclusive breastfeeding rates at 3 months after delivery. The results of random effect model analysis showed that mHealth-based interventions significantly improved the rate (OR 3.05, 95% CI 1.97-4.73; P <.001; I 2 =70%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of nine studies [ 4 , 5 , 7 , 8 , 11 , 12 , 14 , 17 , 19 ] reported exclusive breastfeeding rates at 3 months after delivery. The results of random effect model analysis showed that mHealth-based interventions significantly improved the rate (OR 3.05, 95% CI 1.97-4.73; P <.001; I 2 =70%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of three [ 5 , 12 , 20 ] studies reported the rate of infant health problems. The results of fixed effects model analysis showed that mHealth-based interventions significantly reduced health problems in infants compared with usual care (OR 0.62, 95% CI 0.43-0.90; P =.01; I 2 =0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Leahy-Warren and McCarthy [11], maternal efficacy can also be perceived as a precursor to parenting skills, and it has been shown that maternal and child attributes, interventions for antenatal care [1], and the quality of marriage [12,23] predict MPSE. Moreover, this study's finding that social support acts as a predictor of MPSE agrees with previous results [13][14][15].…”
Section: Plos Onementioning
confidence: 99%
“…Maternal parenting self-efficacy (MPSE) is one of the critical elements of maternal transformation as a woman moves into parenthood. A mother's self-efficacy as a parent not only affects her own mental health, it also influences the psychological development of her infant [1,2]. The postpartum period can be a depressing stage in any parent's life, but particularly in women because it is during this time that the reality of caring for a newborn becomes tangible [3].…”
Section: Introductionmentioning
confidence: 99%